2009
DOI: 10.1590/s1982-56762009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização genética e fenotípica de isolados de Pyricularia grisea do trigo

Abstract: RESUMO O uso de ferramentas moleculares e avaliações da virulência de Pyricularia grisea, agente causal da brusone do arroz e do trigo, têm permitido identificar variantes do patógeno, especialmente aqueles que ocorrem na cultura do arroz. Nesse sentido, os marcadores microssatélites já demonstraram que são eficientes para classificar isolados de P. grisea em grupos geneticamente relacionados. Os objetivos deste trabalho foram caracterizar a diversidade genética de 18 isolados de P. grisea do trigo com o auxíl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 12 publications
(19 reference statements)
3
22
0
3
Order By: Relevance
“…According to Cruz et al (2009), the following conditions are favorable for the development of the disease: high precipitation, temperatures between 24 and 28°C, cloudy days, and high relative humidity. These authors found that the incidence of the disease advanced during two seasons with spray irrigation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Cruz et al (2009), the following conditions are favorable for the development of the disease: high precipitation, temperatures between 24 and 28°C, cloudy days, and high relative humidity. These authors found that the incidence of the disease advanced during two seasons with spray irrigation.…”
Section: Resultsmentioning
confidence: 99%
“…A presença de alelos nulos em vários organismos é citada na literatura (BRONDANI et al, 2000;CRUZ et al, 2009;SANTOS et al, 2010) e, embora isso possa dificultar as análises, esses alelos não devem ser descartados, pois refletem uma nova fonte de variabilidade genética e podem ser usados na discriminação de indivíduos. No lócus MB02, ocorreu um alelo extra em alguns dos isolados, alelo este que não era esperado, uma vez que o FOC é um organismo haplóide (BENTLEY et al, 1998).…”
Section: Methodsunclassified
“…The fungus infects the plant, after wheat heads are emerged, through the rachis of the spikes. The disease develops to severe levels at warmer temperatures (18 to 28°C), high relative humidity (> 90%), extended periods of dew or rain (> 15 h) and cloudy days (Lima 2004;Cruz et al 2009;Kohli et al 2011). Severe epidemics may lead to yield losses of up to 74% (Goulart et al 2007) due to damage in the rachis that affects the translocation of nutrients and photosynthates to grains and may cause premature death of spike above the infection site (Cruz and Valent 2017;Rodrigues et al 2017).…”
Section: Introductionmentioning
confidence: 99%